My doctorate’s journey / Nur Syazwanie Mansor - Mansor, Dr. Nur Syazwanie (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.